2004
DOI: 10.7205/milmed.169.11.856
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects of Percutaneous Poisoning by the Chemical Warfare Agent VX: Effects of Application Site and Decontamination

Abstract: O-ethyl S-(2-diisopropylaminoethyl) methylphosphonothioate (VX) is an extremely toxic organophosphate nerve agent that has been weaponized and stockpiled in a number of different countries, and it has been used in recent terrorist events. It differs from other well-known organophosphate nerve agents in that its primary use is as a contact poison rather than as an inhalation hazard. For this reason, we examined the effects of application site and skin decontamination on VX toxicity in anesthetized domestic swin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 16 publications
2
30
0
Order By: Relevance
“…The toxicokinetics of VX following skin application in the guinea pig have shown a delayed penetration through the skin [10], resulting in a delayed appearance of cholinergic signs [12,19]. It is obvious that this delayed penetration of VX through the skin contributes to the variation with regard to onset times of clinical signs in the present study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The toxicokinetics of VX following skin application in the guinea pig have shown a delayed penetration through the skin [10], resulting in a delayed appearance of cholinergic signs [12,19]. It is obvious that this delayed penetration of VX through the skin contributes to the variation with regard to onset times of clinical signs in the present study.…”
Section: Discussionmentioning
confidence: 86%
“…In spite of the use of anaesthetized animals, the variability in toxicokinetics was considerable. The latter variable and delayed absorption of VX from the skin may have important implications for military or civilian first responders with respect to triage, decontamination and therapeutic drug regimens [11,12]. The present study was designed to investigate the central and peripheral effects of exposure to percutaneous VX in hairless guinea pigs, in order to broaden the scope for possible treatment.…”
Section: Introductionmentioning
confidence: 97%
“…For in vivo studies, experimental animal models, such as rodents (rat, mouse, guinea pig) or rabbits have been used first (Ballantyne and Marrs, 1992;Liu et al, 1999). More recently, in vivo approaches using the domestic pig have demonstrated a real interest of this model for CWA skin absorption studies (Dorandeu et al, 2007;Hawkins and Reifenrath, 1984;Simon and Maibach, 2000;Amitai et al, 2003;Chilcott et al, 2003Chilcott et al, , 2005bHamilton et al, 2004;Duncan et al, 2002;Van der Schans et al, 2003;Kadar et al, 2003). Nevertheless, the in vivo swine model showed many disadvantages, such as the supply and stabling of a large number of pigs or the handling of these animals.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, dilution was found to elevate skin permeation in vitro (13,14), which could possibly lead to an earlier manifestation of cholinergic signs and higher VX toxicity in vivo. On the other hand, Hamilton et al (15) found little or no effect of dilution on VX absorption. The extreme toxicity of agent VX is caused by a preferential reaction with AChE, contrary to G-agents which are more willing to be hydrolyzed by other ChE (2).…”
Section: Acute Toxicity Of Opsmentioning
confidence: 99%
“…The response time is an important factor which infl uences the effectiveness of the decontamination (15,17,25,26). In this study, decontamination was performed 2 min after exposure and the effectiveness would have certainly been decreased had the treatment been delayed.…”
Section: Decontamination Of Opmentioning
confidence: 99%